2010
DOI: 10.2478/s11756-010-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and molecular (RAPD) analysis of six Serapias taxa from Croatia

Abstract: Abstract:The morphometric analyses and genetic variability assessed by RAPD markers have been used to analyse relations among six Serapias taxa from Croatia (S. istriaca, S. pulae originally described as hybrid, S. ionica, S. vomeracea, S. lingua and S. cordigera). S. istriaca distributed in southern Istria and the island of Lošinj and S. pulae stenoendemic taxon distributed only in southern Istria S. ionica is endemic to the Ionian and Dalmatian islands, while the remaining taxa are more widely distributed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(19 reference statements)
1
5
0
1
Order By: Relevance
“…The polymorphism level found in this study was similar to that reported by Rodrigues et al (2005), Junqueira et al (2010), andHršak et al (2011), with polymorphism values of 97, 95.06, and 92.00%, respectively. These polymorphisms are considered high, indicating that the mother plants studied constitute a representative sample of the genetic diversity of gabiroba.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The polymorphism level found in this study was similar to that reported by Rodrigues et al (2005), Junqueira et al (2010), andHršak et al (2011), with polymorphism values of 97, 95.06, and 92.00%, respectively. These polymorphisms are considered high, indicating that the mother plants studied constitute a representative sample of the genetic diversity of gabiroba.…”
Section: Discussionsupporting
confidence: 90%
“…However, the quantification of phenotypic diversity among accessions is feasibly only when the phenotypic divergence reflects the genetic divergence (Dias and Kageyama, 1991) because environmental effects and gene action can complicate this assessment (Andrade et al, 2011). The results of the combination of both tools (morphometry and RAPD makers) have proven to be satisfactory, as reported by Rodrigues et al (2005), Hršak et al (2011), Nandini et al (2011, and others. The purpose of this study was to characterize the genetic diversity of gabiroba matrices from several locations in the State of Goiás on the basis of morphological data and RAPD markers, and to morphologically characterize the progenies of these matrices.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Individuals with intermediate morphological characteristics are not necessarily hybrids. Morphological traits in combination with molecular markers (RAPDs) are used to assess genetic variability in plant species or to identify hybrids (Yüzbaşıoğlu et al, 2008;Hrṧak et al, 2011;Ferreyra et al, 2013;Song et al, 2015). In recent years RAPD have been used for studies between different A. unedo genotypes (Takhrouni and Boussaid, 2010;Lopes et al, 2012;Gomes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Protected Landscape of Donji Kamenjak (further on PLDK) and Medulin archipelago has been protected since 1996. More than 500 vascular plant species have been recorded in earlier floristic researches (Tommasini, 1873;Freyn, 1877;Perko, 1998;Starmühler, 1998Starmühler, , 2004Starmühler, , 2010Topić and Šegulja, 2000;Hršak et al, 2011), among which many are protected at national level (Vuković et al, 2011(Vuković et al, , 2013Anonymus, 2013a, b). Therefore, Rt Kamenjak as a southernmost promontory of PLDK was recently proclaimed as Important Plant Areas (IPA) as an important area of plant diversity for the Republic of Croatia (Vuković, 2010).…”
Section: Introductionmentioning
confidence: 99%